1994
DOI: 10.1002/ajmg.1320540111
|View full text |Cite
|
Sign up to set email alerts
|

Genomic scan for genes predisposing to schizophrenia

Abstract: We initiated a genome-wide search for genes predisposing to schizophrenia by ascertaining 9 families, each containing three to five cases of schizophrenia. The 9 pedigrees were initially genotyped with 329 polymorphic DNA loci distributed throughout the genome. Assuming either autosomal dominant or recessive inheritance, 254 DNA loci yielded lod scores less than -2.0 at theta = 0.0, 101 DNA markers gave lod scores less than -2.0 at theta = 0.05, while 5 DNA loci produced maximum lod scores greater than 1: D4S3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(103 citation statements)
references
References 71 publications
2
99
1
1
Order By: Relevance
“…14 Although CYP1A2 by itself has never been implicated in pathogenesis of schizophrenia, the neighboring loci (15q13-15) have all been implicated. [20][21][22][23] CYP1A2 (15q21) is located in the vicinity of nicotinic receptors CHRNA3, CHRNA5 and CHRNB4, localized at 15q24. CYP1A2 mRNA has been detected in the rat brain (cortex, cerebellum, brain stem, thalamus, hippocampus and striatum 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…14 Although CYP1A2 by itself has never been implicated in pathogenesis of schizophrenia, the neighboring loci (15q13-15) have all been implicated. [20][21][22][23] CYP1A2 (15q21) is located in the vicinity of nicotinic receptors CHRNA3, CHRNA5 and CHRNB4, localized at 15q24. CYP1A2 mRNA has been detected in the rat brain (cortex, cerebellum, brain stem, thalamus, hippocampus and striatum 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome 15q13-15 has been found to be associated with schizophrenia in genome wide scans [30][31][32] although the criteria for linkage were fulfilled in only one study using a subtype Periodic Catatonia (15q15 at position 35.3 cM, LOD score ¼ 3.57, P ¼ 2.6 Â 10 À5 ). 32 Freedman et al 33 reported positive linkage of the abnormality in P50 suppression with D15S1360, a dinucleotide repeat present o120 kbp from the 5 0 end of the coding region of the alpha 7-nicotinic receptor gene (CHRNA-7), assuming an autosomal dominant mode of transmission (LOD score ¼ 5.3, Y ¼ 0.0, Po0.0001 33 ).…”
Section: Association Of Cyp1a2 Polymorphisms With Tardive Dyskinesiamentioning
confidence: 99%
“…Genotyping was performed using standard techniques. 21 Marker allele frequencies for the K1583 genome scan were estimated from 56 marry-in spouses taken from seven pedigrees. Marker allele frequencies for the chromosome 2 region were estimated from 94 marry-in spouses from all 17 typed pedigrees.…”
Section: Genotypingmentioning
confidence: 99%